Protecting National Energy: The Legal Framework on Domestic Gas in Nigeria and Lessons from Indonesia - Viko, Iyadah John; Ecoma, Bonnievolo Eson (Fakultas Hukum Universitas Hang Tuah, 2025)
Nigeria is endowed with vast natural resources and significant gas reserves, and is often called a “province of gas.” In spite of the huge gas reserves available, the country prioritises crude oil over gas, leading to inefficiencies and waste in the gas sector. Although gas flaring and venting are globally recognised as harmful and wasteful practices, they have persisted in the country for over six decades due to various challenges. This unhealthy situation has resulted in unreliable gas supply to the power sector and raised questions about the adequacy and efficacy of the legal and regulatory framework for domestic gas protection and utilisation in the country. With the enactment of the Petroleum Industry Act in 2021, the legal and regulatory landscape has been transformed to provide for an efficient, effective, and commercially viable petroleum industry that enhances gas protection and utilisation. Relying on the doctrinal legal research methodology, the paper sought to analyse extant laws, regulations, and institutions responsible for domestic gas protection and utilisation in Nigeria, with a view to ascertaining their adequacy and efficacy. The analysis provided core insights and revealed that although the current framework is laudable and quite adequate, certain inherent flaws could undermine its objectives and hinder effective gas protection and utilisation. With comparative insights from Indonesia, the paper recommended statutory reforms and effective implementation of laws and regulations. By reforming the legal framework and implementing laws effectively, Nigeria can fully unlock its gas potential and promote a more efficient and sustainable gas sector.